2017
DOI: 10.1016/s2095-3119(16)61608-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of salt stress on rice growth, development characteristics, and the regulating ways: A review

Abstract: Rice (Oryza sativa L.) is highly susceptible to the rhizosphere salinity than other cereals. High sensitivity has been observed, mainly at vegetative and reproductive stages in rice. It is the duty of plant physiologists to comprehend the growth, development, and physiological processes of rice plants under stress. This paper includes the overview of rice growth and developmental processes influenced by salt stress and the regulation pathways involved in these processes. It also includes the promising salt tol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
96
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 186 publications
(124 citation statements)
references
References 158 publications
(183 reference statements)
2
96
0
3
Order By: Relevance
“…The seedling stage is a crucial and particularly vulnerable stage in the life cycle of crops and healthy and strong seedlings guarantee a considerable yield in a population. As a major abiotic stress worldwide, salt at low concentration suppresses plant growth and productivity while high salinity can cause the death of plants [4,[35][36][37]. Hussain et al [37] reported that the root length, root number, and shoot length of rice seedlings were significantly decreased in response to salt stress, and higher salt concentrations caused higher leaf mortality in all rice cultivars at the early seedling stage [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The seedling stage is a crucial and particularly vulnerable stage in the life cycle of crops and healthy and strong seedlings guarantee a considerable yield in a population. As a major abiotic stress worldwide, salt at low concentration suppresses plant growth and productivity while high salinity can cause the death of plants [4,[35][36][37]. Hussain et al [37] reported that the root length, root number, and shoot length of rice seedlings were significantly decreased in response to salt stress, and higher salt concentrations caused higher leaf mortality in all rice cultivars at the early seedling stage [38].…”
Section: Discussionmentioning
confidence: 99%
“…As a major abiotic stress worldwide, salt at low concentration suppresses plant growth and productivity while high salinity can cause the death of plants [4,[35][36][37]. Hussain et al [37] reported that the root length, root number, and shoot length of rice seedlings were significantly decreased in response to salt stress, and higher salt concentrations caused higher leaf mortality in all rice cultivars at the early seedling stage [38]. Singh et al [17] reported a significant loss in growth (such as short plant height, lower biomass, and less photosynthetic pigments) and gross photosynthesis in tomato seedlings treated with salt.…”
Section: Discussionmentioning
confidence: 99%
“…Plant growth and yield reduction induced by soil salinity might occur due to the changes in numerous physiological and biochemical attributes, i.e., the reduction of leaf chlorophyll content (Chl a, b, carotenoids) and photosynthesis capacity, as well as the alteration of energy in the mechanisms of ion exclusion, osmotic adjustment, and nutrient imbalance [54]. Mostly, salt-affected soils affect crops in three ways: osmotic stress, ion imbalance, and oxidative damage [55]. The main response of salt-affected soils is the toxic effects of sodium (Na + ) and chloride (Cl − ) ion accumulation in plant tissues [55,56].…”
Section: Impacts Of Salinity On Physiological Traitsmentioning
confidence: 99%
“…Mostly, salt-affected soils affect crops in three ways: osmotic stress, ion imbalance, and oxidative damage [55]. The main response of salt-affected soils is the toxic effects of sodium (Na + ) and chloride (Cl − ) ion accumulation in plant tissues [55,56]. It has been proven that plants under salinity stress accumulate more Na + ions, resulting in the agitation of ionic balance and plant metabolism and stimulation of oxidative damage, while the K + ion status in plant tissues helps plants develop tolerance towards soil salinity [9].…”
Section: Impacts Of Salinity On Physiological Traitsmentioning
confidence: 99%
“…Rice production is affected by several factors including the environmental stress. It is known that rice is sensitive to salt stress, especially during seedling stages [3,4]. Salt stress is mainly caused by high concentration of sodium chloride (NaCl) that reduces the ability of rice to absorb water from the soil and induces chlorophylls degradation [5].…”
Section: Introductionmentioning
confidence: 99%